Single-centre experience with the frozen elephant trunk technique in 251 patients over 15 years - Shrestha, Malakh Lal; Karck, Matthias (European journal of cardio-thoracic surgery, 2017)
AbstractOBJECTIVES. Our goal was to present our 15-year experience (2001-2015) with the frozen elephant trunk (FET) technique.METHODS. A total of 251 patients